2022
DOI: 10.1021/acs.nanolett.2c00349
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Surface Engineering with Heparosan Polysaccharide Reduces Serum Protein Adsorption and Enhances Cellular Uptake

Abstract: Nanoparticle modification with poly­(ethylene glycol) (PEG) is a widely used surface engineering strategy in nanomedicine. However, since the artificial PEG polymer may adversely impact nanomedicine safety and efficacy, alternative surface modifications are needed. Here, we explored the “self” polysaccharide heparosan (HEP) to prepare colloidally stable HEP-coated nanoparticles, including gold and silver nanoparticles and liposomes. We found that the HEP-coating reduced the nanoparticle protein corona formatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 52 publications
2
41
0
Order By: Relevance
“…In Figure S1, we demonstrated that HEP-coated gold nanoparticles (HEP-AuNPs) efficiently target antigen-presenting cells, such as macrophages and dendritic cells, consistent with our previous findings . This study used RAW 264.7 macrophages and DC 2.4 dendritic cells as model immune cells.…”
supporting
confidence: 88%
See 3 more Smart Citations
“…In Figure S1, we demonstrated that HEP-coated gold nanoparticles (HEP-AuNPs) efficiently target antigen-presenting cells, such as macrophages and dendritic cells, consistent with our previous findings . This study used RAW 264.7 macrophages and DC 2.4 dendritic cells as model immune cells.…”
supporting
confidence: 88%
“…To further validate the time-dependent cellular internalization, we performed confocal laser scanning microscopy (CLSM) to monitor the nanoparticle uptake behavior in real-time in RAW 264.7 macrophages up to 7 h post-incubation (Figure C,D; Figure S4). The HEP-AuNPs were imaged label-free via nanoparticle light scattering and were mainly present surrounding the cell membrane after 1 h of incubation. , We observed strong intracellular nanoparticle signals at 4.5, 5, and 7 h time points post-incubation. To corroborate the intracellular localization, we subsequently visualized the spatial distribution of nanoparticles in RAW 264.7 macrophages at 3, 6, and 24 h (Figure E and Figure S5) and DC 2.4 dendritic cells at 3 and 24 h (Figure S6) post-incubation by transmission electron microscopy (TEM).…”
mentioning
confidence: 85%
See 2 more Smart Citations
“…We then qualitatively assessed nanoparticle association with B cells with CLSM using a label-free light scattering approach to visualize AuNPs associated with B cells. , Due to the ability of metallic nanoparticles to scatter light, fluorophores were not required to visualize AuNPs. Interestingly, only B cells exposed to K7C-modified AuNPs had detectable intracellular CLSM light scattering signals (Figure C).…”
mentioning
confidence: 99%